Dynamic modeling and step-climbing analysis of a two-wheeled stair-climbing inverted pendulum robot. (3rd March 2020) - Wardana, A. A.; Takaki, T.; Aoyama, T.; Ishii, I.
ABSTRACT: In this study, the control of a two-wheeled stair-climbing inverted pendulum robot and its climbing motion are analyzed and discussed. The robot adopts a state-feedback controller with a feed-forward constant to stabilize the body and achieve step-climbing motion. The control parameter is considered based on the dynamic model motion on a flat surface and the static model of motion on the step. For climbing stairs with a narrow step tread, a constant torque is applied to reduce the space required for recovering the body stability after climbing. The stability of the robot is numerically analyzed by analyzing the orbital stability of its limit cycle. The stability analysis shows that the control method can achieve a stable stair-climbing motion. The effectiveness of the control method is demonstrated through an experiment. The result indicates that the robot can climb the stairs, and the required time for climbing a single step is approximately 1.8 s. GRAPHICAL ABSTRACT: